Pengaruh Penggunaan Kontrasepsi Hormonal terhadap Kinerja Fisik dan Kebugaran pada Wanita Usia Subur: Tinjauan Literatur dan Implikasinya dalam Praktik Kebidanan - Damayanti, Tri Yunita Fitria (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aimed to synthesise current findings on the effect of hormonal contraceptive use on physical performance and fitness in women of childbearing age and its implications for midwifery practice. The method used was a systematic literature review of Scopus indexed articles from 2010-2023, which addressed the effects of hormonal contraception (pills, injections, IUDs and implants) on muscle strength, endurance, recovery and exercise adaptation in active women or athletes. Data were analysed narratively by grouping findings based on physiological and psychosocial aspects. Results showed that most studies found no significant effect of hormonal contraceptives on strength and endurance, but some studies showed changes in metabolic responses, muscle recovery, and exercise motivation. Variations in impact depended on the type of contraceptive and the context of physical activity. In obstetric practice, it is important to consider these factors in counselling for physically active women. In conclusion, hormonal contraceptive use does not significantly reduce physical performance, but the effects on recovery and psychosocial aspects need special attention. Midwives play an important role in providing appropriate counselling and multidisciplinary collaboration with sports health professionals is needed to support women's optimal reproductive health and physical fitness.